Methods of working coal and metal mines planning and operations - Woodruff, Seth D. (Oxford Pergamon Press, 1966)
Methods of Working Coal and Metal Mines, Volume 3 discusses the extraction of mineral deposits, which involves the driving of development openings, from the surface or a central shaft, to the “block out” portions of the deposit. This book is divided into three parts. Part A describes the coal mining methods, which include pillar mining systems and long-wall mining. Economics of coal face mechanization is also discussed. In Part B, the classification of stoping systems, which is comprised of pillar-supported stopes, timber and fill supported stopes, and slicing or caving systems, is elaborated. This part also emphasizes the mining bedded metalliferous ores, as well as the costs and other factors affecting the choice of mining systems. Part C deliberates the surface mining methods, which consist of strip mining of coal, open-pit mining, and stability of pit slopes. This publication is intended for mining engineers, but is also useful to students and researchers conducting work on the application of extracting and processing minerals.--Provided by publisher.
v. 1. Theory and application of rock mechanics to roof control and support problems.--v. 2. Ground support methods.--v. 3. Planning and operations.
Keywords: Mining engineering; Coal mines and mining; Electronic books